Phase 2 study of low‐dose clofarabine plus cytarabine for patients with higher‐risk myelodysplastic syndrome who have relapsed or are refractory to hypomethylating agents. Issue 4 (14th October 2016) - Jabbour, Elias; Faderl, Stefan; Sasaki, Koji; Kadia, Tapan; Daver, Naval; Pemmaraju, Naveen; Patel, Keyur; Khoury, Joseph D.; Bueso‐Ramos, Carlos; Bohannan, Zachary; Ravandi, Farhad; Borthakur, Gautam; et al.
Abstract : BACKGROUND: The outcome of patients with higher‐risk myelodysplastic syndromes (MDS) after hypomethylating agent (HMA) failure is poor. This study evaluated the safety and activity of a combination of low‐dose clofarabine and cytarabine for these patients. METHODS: Seventy patients with higher‐risk MDS who had no response, progressed, or relapsed after at least 4 cycles of HMA therapy were treated. RESULTS: The median age was 72 years. Thirty‐nine percent of the patients had high‐risk disease according to the International Prognostic Scoring System, and 50% of the patients had poor‐risk cytogenetics. Twenty‐three percent of the patients had therapy‐related MDS. The median number of prior cycles of HMA was 6 (range, 4‐45). The overall response rate was 44%. The 6‐week mortality rate was 9%. Grade 3 and higher nonhematologic toxicities were rare, but infections occurred in 52% of the patients, and fever of unknown origin occurred in 33%. The median overall survival (OS) was 10 months (95% confidence interval, 1‐37 months). Thirteen percent of the patients underwent allogeneic stem cell transplantation. The responding patients had a median OS of 22 months, whereas the nonresponding patients had a median OS of 4 months. A complex karyotype was associated with worse response rates and OS. CONCLUSIONS: The combination of low‐dose clofarabine and cytarabine is clinically active in these patients with few treatment options. Cancer 2017;123:629–637. © 2016 American Cancer Society . Abstract : The effectiveness of low‐dose clofarabine and cytarabine in higher‐risk myelodysplastic syndrome patients after hypomethylating agent failure is assessed. This dose combination is clinically active in these patients (especially those with diploid cytogenetics) and may be useful as a bridge to allogeneic stem cell transplantation in eligible patients.